Evaluacion de dosis de nitrogeno y fosforo en el cultivo de Pitahaya (Hylocereus undatus) - Lopez Turcios, O.=700 1 Guido Miranda, A.
(En, Es)
ilus., 10 ref.
Keywords: HYLOCEREUS UNDATUS; ABONOS NITROGENADOS; ABONOS FOSFATADOS; ABONOS POTASICOS; OLIGOELEMEMTOS; RENDIMIENTO; COSTA RICA